Pengaruh Peran Edukator Perawat Terhadap Kemandirian Keluarga Dalam Merawat Klien Gangguan Jiwa - Hertiana Hertiana; Ariyanti Saleh (Celebes Health Journal, 2019)
Abstract The role of the community health nurse educator is expected to increase the independence of the family. The aim of public health nurse educator by giving health education with modelling approach to family regarding knowlegdge, attitude, and family independency. The research used quasi experiment pre-post control group design. The intervention given was health education with modeling approach about the treatment of psychiatric clients. The research was conducted in the working area of PKM pontap, Notrh Wara, and South Wara of Palopo City. The samples were 42 people consisted of 21 people of intervention group and 21 people of control group. The results of wilcoxon test indecate that there is a significant difference between intervention group and control group regarding knowledge (p=0.000, p=0.739), attitude (p=0.000, p=0.107), independency (p=0.000, p=0,157). Mann Whitney test of the two groups indicate knowledge (p=0.000), attitude (p=0.000), and independency (=p=0.000). health education with modeling apporoach performed by perkesmas nurses is effective to improve knowledge, attitude, and independency of family in giving treatment to family members suffering from mental disorder. Keywords: educators’role, health education, family, independency. Abstrak Peran edukator perawat khususnya perawat kesehatan masyarakat (Perkesmas) diharapkan mampu meningkatkan kemandirian keluarga. Penelitian ini bertujuan untuk mengidentifikasi efektivitas peran edukator perawat perkesmas melalui pemberian pendidikan kesehatan terhadap kemandirian keluarga dalam merawat anggota keluarga yang mengalami gangguan jiwa. Penelitian ini menggunakan desain quasi eksperiment pre-post control group design. Intervensi yang diberikan berupa pemberian pendidikan kesehatan dengan pendekatan modelling tentang perawatan klien gangguan jiwa.Penelitian ini dilaksanakan di wilayah Kota Palopo. Keseluruhan sampel berjumlah 42 orang terdiri atas 21 orang kelompok intervensi dan 21 orang kelompok kontrol. Hasil uji wilcoxson membuktikan ada perbedaan yang padakelompok intervensi dan kontrol yaitu kemandirian (p=0,000, p=0,157).Uji mann whitney antara kedua kelompok didapat data kemandirian p=0,000. Pendidikan kesehatan yang dilakukan perawat perkesmas efektif dalam meningkatkan kemandirian keluarga dalam merawat klien gangguan jiwa. Kata kunci: Peran edukator,pendidikan kesehatan, keluarga, kemandirian.